Hybrid deep learning model-based prediction of images related to cyberbullying - Elmezain, Mahmoud; Malki, Amer; Gad, Ibrahim; Atlam, El-Sayed (Zielona Góra: Uniwersytet Zielonogórski)
Cyberbullying has become more widespread as a result of the common use of social media, particularly among teenagers and young people. A lack of studies on the types of advice and support available to victims of bullying has a negative impact on individuals and society. This work proposes a hybrid model based on transformer models in conjunction with a support vector machine (SVM) to classify our own data set images.
Keywords: cyberbullying; ResNet50; MobileNetV2; support vector machines